2017
DOI: 10.3390/ijms18030641
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light-Emitting Diode Irradiation on Growth Characteristics and Regulation of Porphyrin Biosynthesis in Rice Seedlings

Abstract: Abstract:We examined the effects of light quality on growth characteristics and porphyrin biosynthesis of rice seedlings grown under different wavelengths from light emitting diodes (LEDs). After 10 days of exposure to various wavelengths of LEDs, leaf area and shoot biomass were greater in seedlings grown under white and blue LEDs than those of green and red LEDs. Both green and red LED treatments drastically decreased levels of protoporphyrin IX (Proto IX) and Mg-porphyrins compared to those of white LED, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 39 publications
(45 reference statements)
8
6
0
Order By: Relevance
“…1b). This may have been due to the responses of the leaves to different optical signals, which is consistent with the results of previous studies on rice and lettuce [39,40]. However, studies have shown different results for Camptotheca acuminata Decne.…”
Section: Discussionsupporting
confidence: 90%
“…1b). This may have been due to the responses of the leaves to different optical signals, which is consistent with the results of previous studies on rice and lettuce [39,40]. However, studies have shown different results for Camptotheca acuminata Decne.…”
Section: Discussionsupporting
confidence: 90%
“…This may be attributed to the broad-band light filters used in earlier studies, which could transmit a mixture of wavelengths that may have confounded results. The intense greening at blue wavelengths observed in this study is consistent with previous studies in leaf tissues, which showed enhanced activity of key chlorophyll enzymes [16,17], leading to higher chlorophyll accumulation as compared to red light [18][19][20][21].…”
Section: Plos Onesupporting
confidence: 92%
“…In Chinese cabbage, red:blue 6:1 and blue light increased chlorophyll concentrations significantly, while red light decreased chlorophyll accumulation as a result of reductions in chlorophyll precursors ALA, Proto IX, Mg-Proto IX and protochlorophyllide [ 32 ]. In rice seedlings, blue light led to chlorophyll a levels similar to those of white light illuminated plants, as did with levels of Proto IX and Mg-Proto IX, while red light decreased the same precursors [ 34 ]. In the same paper, blue light upregulated the transcription of HO2 , encoding heme oxygenase and of CHLD , encoding the D subunit of Mg-chelatase, while red light increased the transcription levels of PPO1 , encoding protoporphyrin oxidase, underlining the importance of these genes in plant adaptation to altered light environments.…”
Section: Discussionmentioning
confidence: 99%